Development Global Competitive Advantage at PT Tiphone Mobile Indonesia, Tbk Case Study using 4C’s Framework Model - Aryo Wicaksono; Rivaldi Arissaputra; Popy Rufaidah (AIBPM Publisher, 2018)
This paper discusses about the application of global competitive advantage with the 4C's Framework model (Hao Ma, 2004) that consists of Creation, Competition, Cooperation and Co-option variables in PT Tiphone Mobile Indonesia, Tbk.. The research method used is case study and SWOT Analysis method. The research provides a managerial impact to the company that is under study, namely the implementation of 4C’s Framework model so the company has the advantage of competing globally. The Company achieves global competitive advantage based on ownership-based, access-based, and proficiency-based through the implementation of Creation and Innovation, Competition, Cooperation, and Co-option.